A real options framework for platform-based product family design - Lim, Ching Moi (2008)
Product family design and platform-based product development have been well recognized as an effective means to achieve mass customization. Investing into product families which build on platforms and shared modules, installs flexibility for a company to accommodate future customization requirements, while taking a risk due to increased complexity in design and production. It is crucial to properly identify and capitalize on favorable and worthwhile opportunities of future investments while mitigating the possible losses from adverse market development. Accordingly, the fundamental research issue of justifying the relative economic value of product families and platforms is addressed.